Implementation of an Ethnomathematics-Based Deep Learning Approach in Mathematics Education: A Case Study of Teaching Practices in Secondary Schools - Kusuma, Jaka Wijaya; Hamidah, Hamidah (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
Purpose: This study aims to describe the implementation of an ethnomathematics-based deep learning approach in mathematics education at the secondary school level. The primary focus of the study is to analyse how teachers integrate local cultural contexts into the learning process to foster deep conceptual understanding, critical thinking, and reflection.Methods: This study employed a qualitative, descriptive case study design. The research subjects consisted of one mathematics teacher and 30 eighth-grade students at a secondary school that implements local culture-based learning. Data were collected through participant observation, semi-structured interviews, and documentation of instructional materials and student work. Data analysis was conducted using the interactive model by Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and conclusion. Data validity was ensured through triangulation of sources and techniques.Results: The findings indicate that the teacher successfully integrated elements of local culture, such as batik motifs and traditional games, as an initial context for exploring concepts in geometry and social arithmetic. Learning took place through stages of exploration, group discussion, contextual problem-solving, and reflection—hallmarks of deep learning. Students demonstrated increased active engagement and the ability to connect mathematical concepts with cultural phenomena around them. However, implementation faced challenges, including time constraints and the complexity of designing activities that deeply connect culture with mathematical concepts.Conclusion: An ethnomathematics-based deep learning approach has the potential to create meaningful, contextually relevant, and student-centred mathematics learning. The integration of local culture not only aids conceptual understanding but also strengthens students’ cultural identity. This study recommends developing instructional modules and providing teacher training to optimise the implementation of this approach